2022
DOI: 10.3389/fmed.2022.821908
|View full text |Cite
|
Sign up to set email alerts
|

Academic and Social Impact of Menstrual Disturbances in Female Medical Students: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe stressful academic schedule of medical students poses an obvious challenge to their daily lifestyle. Psychosomatic discomfort poses a significant risk for inaccurate self-medication for ameliorating menstrual complications and feeling better, thus directly impacting personal and academic wellbeing.ObjectiveThe impact of menstrual disturbances on academic life is not extensively explored. Therefore, the primary objective of this research was to probe the prevalence of menstrual disturbances and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…Symptoms are not limited to females with menstrual disorders, such as oligomenorrhea and amenorrhea, but are also reported by females with a normal menstrual cycle (NMC) ( Roomruangwong et al, 2021 ; Righi and Barroso, 2022 ). During the late luteal phase, i.e., the premenstrual phase (PM), a systematic review reported a pooled prevalence of 51.3% of premenstrual syndrome in female students, with various reported self-perceived symptoms such as cyclic mood disorders, somatic or affective disorders, and severe fatigue ( Maity et al, 2022 ). This prevalence varies from 32% to 95%, with a majority of studies conducted outside Europe ( Yamamoto et al, 2009 ; Pinar et al, 2011 ; Hamaideh et al, 2014 ; Tolossa and Bekele, 2014 ; Romito et al, 2017 ; Bhuvaneswari et al, 2019 ; Hashim et al, 2019 ; Maity et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Symptoms are not limited to females with menstrual disorders, such as oligomenorrhea and amenorrhea, but are also reported by females with a normal menstrual cycle (NMC) ( Roomruangwong et al, 2021 ; Righi and Barroso, 2022 ). During the late luteal phase, i.e., the premenstrual phase (PM), a systematic review reported a pooled prevalence of 51.3% of premenstrual syndrome in female students, with various reported self-perceived symptoms such as cyclic mood disorders, somatic or affective disorders, and severe fatigue ( Maity et al, 2022 ). This prevalence varies from 32% to 95%, with a majority of studies conducted outside Europe ( Yamamoto et al, 2009 ; Pinar et al, 2011 ; Hamaideh et al, 2014 ; Tolossa and Bekele, 2014 ; Romito et al, 2017 ; Bhuvaneswari et al, 2019 ; Hashim et al, 2019 ; Maity et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the late luteal phase, i.e., the premenstrual phase (PM), a systematic review reported a pooled prevalence of 51.3% of premenstrual syndrome in female students, with various reported self-perceived symptoms such as cyclic mood disorders, somatic or affective disorders, and severe fatigue ( Maity et al, 2022 ). This prevalence varies from 32% to 95%, with a majority of studies conducted outside Europe ( Yamamoto et al, 2009 ; Pinar et al, 2011 ; Hamaideh et al, 2014 ; Tolossa and Bekele, 2014 ; Romito et al, 2017 ; Bhuvaneswari et al, 2019 ; Hashim et al, 2019 ; Maity et al, 2022 ). Always among female students, 72.7% report dysmenorrhea, i.e., painful menstrual cramps and other associated symptoms (low back pain, headache, vomiting, diarrhea, fatigue, or nausea) during the early follicular phase, occurring the first days of menses (ME) ( De Sanctis et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations